Pemanfaatan Artificial Intelligence pada Pembelajaran dan Asesmen di Era Digitalisasi - Arnolus Juantri E. Oktavianus; Lamhot Naibaho; Djoys Anneke Rantung (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
In facing the era of rapidly developing digitalization, the use of Artificial Intelligence (AI) technology has changed the learning paradigm and in-depth assessment as demonstrated through the application of Artificial Intelligence. AI helps teachers to carry out speeches optimally by utilizing the power of AI. However, on the other hand, AI has a negative impact on a person if it is not used properly. One of the advantages of AI is that it can do what humans do. With this advantage, AI can carry out activities carried out by humans, including the implementation of learning and assessment. Therefore, teachers need to utilize artificial intelligence in learning and assessment in the ever-growing digital era. The aim of this research is to investigate the application of AI in the context of learning and assessment, disseminate the methods used, and analyze the positive impact artificial intelligence produces. The research method used in this research is quantitative with a descriptive approach. The research results show that the use of AI in learning and assessment has increased the efficiency, accuracy and personalization of learning. Through machine learning algorithms, AI learning systems can identify individual student needs and deliver appropriate learning content, enabling a more relevant and effective learning experience. Additionally, in the context of assessment, AI has provided solutions for fast and objective automated assessments, reducing teacher workload and providing more in-depth feedback to students. Keywords: Artificial Intelligence; Learning; Assessment; Era of Digitalization